The central limit theorems for sums of the discrete renewal processes - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Алешкявичене. Центральная предельная теорема для сумм дискретных процессов восстановленияA. Aleškevičienė. Centrinė ribinė teorema diskretinių atstatymo procesų sumoms